2014
DOI: 10.1186/2008-2231-22-32
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of verbascoside in medicinal species of Phlomis and their genetic relationships

Abstract: BackgroundThe genus Phlomis (Lamiaceae) is introduced by its valuable medicinal species, of which 17 species are growing wildly and ten of them are exclusively endemic of Iran. The main phytochemical characteristic of this genus is presence of iridoid glycosides including ipolamide, auroside, lamiide and also phenylethanoids such as verbascoside (acetoside) found in Lamiales order.Due to the broad range of biological and pharmacological activities of verbascoside and lack of any report on quantification of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
(19 reference statements)
3
12
0
2
Order By: Relevance
“…Totally, 27 compounds representing 90.52 -98.51% of the total oil were identified in the essential oil of P. olivieri. The main compounds found in the several populations were germacrene D (26.54 Consistently with our results, the major essential oil components of P. olivieri collected in northern part of Iran (Mazandaran and Guilan provinces) were germacrene D, b-caryophyllene, and a-pinene, [14] while Ghassemi et al [15] found hexahydrofarnesyl acetone, spathulenol, germacrene D, b-caryophyllene, and caryophyllene oxide as main constituents in the essential oil of P. olivieri collected from central Iran (Isfahan province). In another report [16] on populations from Damav (Tehran province), the main compounds were germacrene D, b-caryophyllene, a-pinene, and b-selinene.…”
Section: Composition Of the Essential Oilssupporting
confidence: 82%
“…Totally, 27 compounds representing 90.52 -98.51% of the total oil were identified in the essential oil of P. olivieri. The main compounds found in the several populations were germacrene D (26.54 Consistently with our results, the major essential oil components of P. olivieri collected in northern part of Iran (Mazandaran and Guilan provinces) were germacrene D, b-caryophyllene, and a-pinene, [14] while Ghassemi et al [15] found hexahydrofarnesyl acetone, spathulenol, germacrene D, b-caryophyllene, and caryophyllene oxide as main constituents in the essential oil of P. olivieri collected from central Iran (Isfahan province). In another report [16] on populations from Damav (Tehran province), the main compounds were germacrene D, b-caryophyllene, a-pinene, and b-selinene.…”
Section: Composition Of the Essential Oilssupporting
confidence: 82%
“…It also often exists in the species of the Lamiales order. 57 Acteoside has several pharmacological properties including being antioxidant, immunosuppressive, and anti-inflammatory. 58 Quercetin is a widely distributed flavonoid in nature; its potential applications include but are not limited to anticancer, anti-inflammatory, and anti-asthmatic.…”
Section: Methodsmentioning
confidence: 99%
“…Three mobile phases were used for the analytical TLC of aucubin including n-butanol (n-BuOH): distilled water (DW) in a proportion of 9 ml: 1 ml [37], n-BuOH: acetic acid (AcOH): DW (8 ml: 2 ml: 10 ml) and isopropanol (IsoPrOH): DW (6 ml: 4 ml) [38]. Three mobile phases were used for the analytical TLC of verbascoside including Ethyl acetate (ETAC): methanol (MeOH): DW (77 ml: 15 ml: 8 ml) [39], ETAC: DW: formic acid (FA) (10 ml: 3 ml: 2 ml) and ETAC: MeOH: DW (100 ml: 16.5 ml: 13.5 ml) [40,41].…”
Section: Chromatographic Analysis For Detection Of Aucubin and Verbasmentioning
confidence: 99%